KLASIFIKASI WARNA HSV PADA CITRA TANGAN MENGGUNAKAN K-MEANS - Safril Nur Abdillah (JUKOMPSI (Jurnal Komputer dan Sistem Informasi), 2022)
The HSV color component is one of the most important elements in an image. In the image processing process, the HSV color feature becomes one of the important roles for the image recognition process. One of the objects used for recognition is hand image. To get the value of the HSV color feature from the hand image, a feature extraction process is needed. Not all HSV color feature extraction yields optimal values. The K-Means method can classify the results of the HSV color feature extraction. The results of the HSV color feature classification are the highest percentage values for each Hue, Saturation, and Value channel.